Supporting dyslexic adults in higher education and the workplace - Brunswick, Nicola, 1970- (Wiley-Blackwell, 2012)
"Supporting Dyslexic Adults provides practical advice in supporting dyslexic adults in education and employment, and guidance on the latest research Provides an important overview of current research and practice in supporting dyslexic adults in education and employment, deftly combining academic understanding with everyday issues Contributors possess a wealth of practical experience in the field which provides an indispensable guide to the subject Case studies are included to capture the immediate experiences of dyslexic adults in education and at work to highlight prevalent issues Offers practical advice to adults with dyslexia, from how to disclose their particular needs to employers and colleagues to legal aspects of dyslexia support Highlights to employers the particular skills and strengths that dyslexic adults can bring to the workplace"-- Provided by publisher.